A bibliometric analysis of acupuncture treatment and cognitive impairment - Yu, Xiaoqi; Lu, Fuchang; Chen, Jinlong; Liu, Xuanjun; Chen, Qingpei (Frontiers in Neurology, 2025)
Cognitive impairment, a prevalent neurological disorder characterized by multisystem dysregulation within the nervous system, has prompted substantial scientific inquiry into complementary therapies. This scientometric investigation systematically examines the evolving bilingual (Chinese-English) research paradigm of acupuncture interventions for cognitive impairment through comparative analysis of 510 publications from the China National Knowledge Infrastructure (CNKI) and 633 articles from Web of Science Core Collection, processed via CiteSpace 6.4.R2. Our multidimensional analysis reveals three principal dimensions: (1) Spatiotemporal evolution demonstrating that scholarly contributions in this domain are predominantly clustered within China. Longitudinal bibliometric analysis demonstrates sustained scholarly productivity in this domain, with annual bilingual (Chinese-English) publication outputs consistently exceeding 40 peer-reviewed articles per annum throughout the 2000–2025 observation window, establishing a robust baseline for continuous knowledge advancement; (2) Network analysis atlas of the research institutions and authors reveals that both research output density and institutional affiliations concentrated in Chinese academic hubs and most authors come from China; (3) Divergent thematic trajectories between linguistic cohorts - Chinese studies emphasize vascular mechanisms, oxidative stress modulation, and pharmacological synergies, whereas English literature prioritizes gut-brain axis interactions, postoperative cognitive recovery, and neuroinflammatory pathways. These findings provide evidence-based insights into acupuncture’s therapeutic mechanisms in cognitive impairment while establishing a conceptual framework to guide future translational studies and clinical protocol optimization in integrative neurology.